Monitoring for the genetic structure of Mezen breed of horses in terms of DNA microsatellites - N. V. Vdovina; I. B. Yuryeva (Вавиловский журнал генетики и селекции)
Mezenskaya horse (Mezenka) is Russia’s aboriginal breed. It is a domestic selection in the northern territories of Arkhangelsk region. The breed is perfectly adapted to the conditions of the Far North, and has a number of valuable economic and biological qualities. At present, it has a limited gene pool and is bred only in the Mezensky district, where one gene pool-breeding farm is operating and so is a number of basic farms, where selection and breeding activities take place with the breed. Due to a small population of Mezen horses, the challenge of preserving its intra-breed diversity is very urgent. To determine the degree of genetic variability in the Mezen population, the alleles-fond was monitored. A comparative analysis of the genetic structure of the breed was done on DNA microsatellites at time-intervals of 10 years (2000, 2010 and 2020). Crista samples of 198 horses were studied in specialized laboratories. It was established that the breed has wide genetic diversity in 17 loci of nuclear DNA. The population’s alleles-fond includes from 128, 139, and 133 alleles respectively (with an average value of 7.53, 8.18, and 7.82 alleles per locus). The most common alleles are AHT4O, AHT5N, ASB2K, ASB23S, CA425N, HMS1J, HMS1M, HMS2H, HMS3M, HMS7L, HTG4M, HTG6O, HTG7K, HTG7O and LEX3M. Mezen horses revealed 6 rare, lowfrequency (0.004–0.056) alleles not found in the horse populations of domestic selection. The average value of the polymorphic level (Ae) in the breed over the years is 4.16, 4.21 and 4.06, respectively. The highest polymorphism is found in locus ASB17 (6.49–6.90–6.76); the lowest, in locus HTG6 (1.71–1.66–1.67) and HMS7 (1.77–1.95–1.77). A slight deficit of heterozygous genotypes (Fis = 0.003) was observed in Mezen horses in 2010. In 2000 and 2020, the observed heterozygosity (Ho) exceeds the expected value (He), which indicates the absence of intra-population inbreeding (Fis = –0.014 and –0.011, respectively). The results obtained testify to the effectiveness of breeding activities carried out to preserve, improve and maintain genetic diversity in the population.